The Role of the Field Emission Effect in the Breakdown Mechanism of Direct‐Current Helium Discharges in Micrometer Gaps. Issue 8 (20th September 2013) - Matejčik, Š.; Klas, M.; Radjenović, B.; Durian, M.; Savić, M.; Radmilović‐Radjenović, M.
Abstract This paper contains results of experimental studies of the direct current breakdown voltage curves and volt‐ampere characteristics of discharges generated in a system consisting of two plane‐parallel tungsten and molybdenum electrodes at separations from 100 µ m to 1 µ m. The measurements were performed in the pressure range from 22.5 Torr to 738 Torr. The results are presented in the form of Paschen curves. Based on the measured breakdown voltage curves, the effective yields have been estimated in the case of different cathode materials. Differences between them are attributed to the influence of the work function of the cathode material on the current‐voltage characteristics due to field emission effect in small gaps and high pressures. At low‐pressures, however, vaporation of impurities from the electrodes material becomes significant. The present paper delivers new data on DC breakdown under these experimental conditions and conditions on the validity of the Paschen law in helium and provides better insight into the role of the field emission and the electrode materials on the breakdown voltage. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)